Living with obesity is related to peer problems in children: A national cross‐sectional study. (14th February 2023) - Beynon, Claire
Abstract : Aim: To assess the association between obesity and problems in peer relations in children (4–15 years) in a large ( n  = 11 279), nationally representative data set. Methods: The chi‐square test was used to compare differences in numbers of children with and without obesity and with and without abnormal peer problem scores. Then multivariable logistic regression was used to determine any association between obesity and peer problems after accounting for deprivation and life‐style factors. Results: The results of the chi‐square test were statistically significant ( P  < 0.05) for all groups except older girls. The multivariable logistic regression identified a small but significant association between children living with obesity and abnormal peer problems, odds ratio (OR) 1.06 (95% confidence interval, CI: 1.04–1.08, P  = 0.001). When explored by subsets of children using sex and age, this association was strongest for girls aged 4–10 years, OR 1.12 (95% CI: 1.07–1.16, P  = 0.001). Conclusion: This is the first nationally representative study of children to identify this association in younger children. Whilst further research is needed to corroborate this finding, as a precautionary measure solutions to improve peer relationships and reduce stigma for school‐aged children living with obesity are indicated.